Design and development of a low-cost inverted pendulum for education - Ferreira, Gonçalo Marques (2022)
Automatic control is present in our daily lives, for example, in elevators, factories, or even toasters and cruise control. The aim of this project is to develop a controller to bal- ance a pendulum on top of a cart with the minimum possible deviation from the vertical position, a system which is often used to represent non-linear systems. To this end, the system was modeled, using Newton’s second law and Lagrange’s equations, in order to find the equations of motion. Then, using Matlab and Simulink, a digital model of the system was implemented, with the LQR, LQG and MPC controllers being tested sepa- rately. The two main steps in the process are reaching the vertical position and stabilizing the pendulum. In the final phase, a 3D printer was controlled, showing its potential as an implementation of the system.